GIS-based Flood Risk Mapping: The Case Study of Kosi River Basin, Bihar, India - Kumar, Niraj; Jha, Ramakar (Engineering, Technology & Applied Science Research, 2023)
Flood risk mapping aims to create an easily read and rapidly accessible map to prioritize the mitigation effects. This study presents an empirical approach to flood risk mapping through the integration of Analytical Hierarchy Process (AHP) and Geographic Information System (GIS) techniques. SRTM 30m DEM is processed using ArcGIS 10.3 software. The study methodology includes the selection of the study area, the identification of the factors responsible for flood and collection of the required data, the generation of the desired thematic layers, and their integration to produce the flood risk map. Geomorphic, hydrologic, and socio-economic analyses are carried out to generate the thematic layers, namely slope, district`s distance to active stream, highest elevation, drainage density, rainfall, population density, and land use-land cover. AHP is used to determine the relative impact weight of the thematic layers. The influence of each thematic layer and the scale values provided based on the weights and score calculated by the AHP are used to integrate the layers in GIS environment to prepare the flood risk map. Consistency ratios are determined from the judgment process to validate the reliability of the proposed approach and results. The study classified the area falling in the basin under different risk zones with Purnia and Madhepura having large areas under high risk. This study may aid decision and policymakers in the evaluation and rapid assessment of flooding phenomena in the region.